Role of SIRT3 in bone homeostasis and its application in preventing and treating bone diseases - Xu, Ke; Li, Jing; Wen, Ruiming; Chang, Bo; Cheng, Yang; Yi, Xuejie (Frontiers in Pharmacology, 2023)
Bone homeostasis refers to the balance between osteoblast-mediated bone formation and osteoclastmediated bone resorption and the maintenance of stable bone mass. SIRT3 is a class of mitochondrial protein deacetylase that influences various mitochondrial functions and is involved in the mechanisms underlying resistance to aging; regulation of bone marrow mesenchymal stem cells, osteoblasts, and osteoclasts; and development of osteoporosis, osteoarthritis, and other bone diseases.Moreover, exercise affects bones through SIRT3. Thus, studies on SIRT3 may provide insights for the treatment of bone diseases. Although SIRT3 can exert multiple effects on bone, the specific mechanism by which it regulates bone homeostasis remains unclear. By evaluating the relevant literature, this review discusses the structure and function of SIRT3, reveals the role and associated mechanisms of SIRT3 in regulating bone homeostasis and mediating bone health during exercise, and highlights the potential pharmacological value of SIRT3 in treating bone diseases.